Designing Al-Based complex confused metallic glasses via chemically complex alloying and crystallization confusion - Wan Kim; Ji Young Kim; Min Kyung Kwak; Eun Soo Park (Materials & Design)
Herein, we report a new alloy design strategy for Al84Ni10RE6 metallic glasses by incorporating multiple equiatomic RE elements (RE = La, Ce, Nd, Gd, Y, Er) while manipulating their electronegativity differences close to the critical value at the transition boundary between eutectic and primary crystallization. The resulting Al84Ni10(NdGdY or NdGdYEr)6 MGs close to Δψcrit, referred to as complex confused metallic glasses (CCMGs), exhibit synergistic effects of complex RE-Al bonding and crystallization confusion. These effects overcome inherent limitations in the supercooled liquid region (ΔTx) and glass forming ability (GFA) observed in Al-Ni-RE MGs with a single RE. Flash DSC study confirmed that the Al84Ni10(NdGdY or NdGdYEr)6 CCMGs show a 50 % reduction of critical cooling rate for glass formation than those of Al84Ni10(La or Er)6 MGs while having ∼ 15 % larger fragility index. The statistical nanoindentation test exhibited the distinct bimodal distribution of shear band nucleation in the Al84Ni10(NdGdY or NdGdYEr)6 CCMGs, with a higher proportion of the soft mode attributed to loosely packed regions-indicative of more fragile behavior mediated by complex RE-Al interaction. Consequently, our study provides a new strategy to optimize multiple key properties of Al-based CCMGs, enabling simultaneous enhancement of GFA, fragility, and intrinsic plasticity.